Phylogenetic relationships within the superfamily Desmodoroidea (Nematoda: Desmodorida), with descriptions of two new and one known species. (10th February 2016) - Leduc, Daniel; Zhao, Zeng
Abstract : Three nematode species of the superfamily Desmodoroidea Filipjev, 1922, were isolated from beach sediments in Wellington, New Zealand, for morphological and molecular analyses. Two of these species, D esmodorella verscheldei sp. nov. and D racograllus ngakei sp. nov., were new to science and are described herein. E psilonema rugatum Lorenzen, 1973, comb. nov., which was originally described from New Zealand material as a subspecies of E psilonema dentatum from Chile, is redescribed and elevated to the rank of species based on cuticular ornamentation. The phylogenetic relationships amongst the three Desmodoroidea families are investigated based on new and existing sequences of the D2 and D3 expansions segments of large subunit ( LSU ) 28S rRNA gene and small subunit ( SSU ) of 18S rDNA gene. Our analyses suggest that the Draconematidae is a sister taxon to the Desmodorinae and Spiriniinae, with the Draconematidae forming a monophyletic crown group and the Desmodorinae and Spiriniinae forming a paraphyletic stem group. Phylogenetic relationships between the Epsilonematidae and Stilbonematinae, however, could not be determined with certainty. The SSU and D2‐D3 of LSU consensus trees indicate that the morphological resemblance between the Draconematidae and Epsilonematidae, which are both characterized by swollen pharyngeal body regions and mid‐posterior body regions with specialized setae, reflects distinct and independently evolved adaptations to their unusual mode of locomotion, with differences in the structure and distribution of specialized setae between the two families also consistent with convergent evolution. We show that the family Desmodoridae and superfamily Desmodoroidea as currently defined are not monophyletic. It was not possible to determine whether the Prodesmodorinae are more closely related to the Desmodoroidea or Microlaimoidea, although it is clear that they do not belong to the Desmodoridae. The single Molgolaiminae sequence available formed a distinct clade together with the superfamily Microlaimoidea, and should therefore be placed with the latter. Clarifying the phylogenetic relationships within the Desmodoroidea will require greater focus on the Pseudonchinae, Molgolaiminae, and Epsilonematidae, for which no or very few sequences are available at present. © 2016 The Linnean Society of London